Knowledge, attitudes and perceptions of antibiotic use and antibiotic resistance among private sector patients and prescribers in South Africa - Farley, Elise (Centre for Infectious Disease Epidemiology and Research (CIDER), 2018)
Antibiotic resistance (ABR), alternately referred to as antimicrobial resistance, has been labelled as the next big global health crisis. If current levels of ABR continue along the same trajectories, by 2050 ABR will cost the lives of 10 million people a year, ABR cannot be stopped but it can be slowed down. ABR occurs because the bacteria evolve to protect themselves from antibiotics. One of the main causes of ABR is the misuse and over prescription of antibiotics. The primary objective of the study is to ascertain the level of knowledge, attitudes and perceptions of appropriate antibiotic use and ABR, among prescribers and patients in private health care in South Africa. The secondary objective of the study is to explore associations between knowledge, attitudes and perceptions of prescribers and patients regarding antibiotic use and resistance. This project consists of three main sections, a proposal, literature review and a journal ready article. All sections focus on ABR. The proposal lays a foundation for the need for the research, and explains how the research will be conducted. The literature review explores the existing evidence on the topic, and the final section is a secondary analysis of cross sectional study data, in which private practice patients and prescribers in South Africa completed a once-off anonymous survey. Data was analysed using Stata,T-tests, chi-squared tests and logistic regression models were used to assess associations between knowledge, attitudes and perceptions of both patients and prescribers. We found that mean knowledge scores among patients (n=403, mean 9 out of 14, standard deviation [SD] 3) and providers (n=175, median 5 maximum 7, IQR 4, 6), were suboptimal and that poor knowledge was associated with perceptions and behaviours as well as prescribing practices that could lead to ABR. Associations between knowledge, attitudes and perceptions of patients and prescribers were explored in multivariate logistic regression models. After adjusting for education and sex, a 1-unit increase in patient knowledge score was associated with the belief that antibiotics will work less well in future if we over-use them now (aOR 1.3; 95% CI: 1.18, 1.43; pvalue <0.001). Prescribers with higher knowledge scores were less likely to report that they prescribe antibiotics when not necessary as antibiotics cannot harm the patient (aOR 0.55; 95% CI: 0.33, 0.91; pvalue 0.02). We also identified a large proportion (58%) of patients who were interested in alternatives to antibiotics and a large proportion (91%) of prescribers wanting educational material to facilitate conversations about resistance with patients. Our study demonstrates gaps in patient and prescriber knowledge that are associated with potentially harmful perceptions and destructive behaviours regarding antibiotic use. These associations, together with our finding that patients and prescribers would like more education on ABR, suggest that educational tools and patient-provider communication tools could promote rational antibiotic use.